1964
DOI: 10.1073/pnas.52.6.1348
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Sv40 Genetic Material Into Adenovirus 7 as Measured by Intranuclear Synthesis of Sv40 Tumor Antigen

Abstract: The surprising finding of Huebner et al.1 that tumors developing in hamsters after inoculation with adenovirus 7 contain the complement-fixing cellular antigen2 of SV40 transformed cells suggested that preparations of adenovirus 7 should -be studied for ability to induce similar antigens in cells growing in culture. Recent observations using the immunofluorescence technique had confirmed that cells transfotmed by SV40 contain a new cellular antigen; this antigen appears to be synthesized in the nucleus and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…The interaction among these harbored viruses may be crucial to the pathological state and may be of particular significance with regard to latent virus infection. Indeed, the replication of numerous viruses has been shown to be affected by the presence of coinfecting viruses such as human adenoviruses and simian virus 40 (12,13) or simian adenovirus SV15 (14), Marek's disease virus and avian leukosis virus (15), and Moloney sarcoma and leukemia viruses (16). To rescue potentially defective HSV in neurons, Brown and coworkers (17) To establish latent infection of HEL cells with HSV-2, we followed previously described protocols (18,19).…”
mentioning
confidence: 99%
“…The interaction among these harbored viruses may be crucial to the pathological state and may be of particular significance with regard to latent virus infection. Indeed, the replication of numerous viruses has been shown to be affected by the presence of coinfecting viruses such as human adenoviruses and simian virus 40 (12,13) or simian adenovirus SV15 (14), Marek's disease virus and avian leukosis virus (15), and Moloney sarcoma and leukemia viruses (16). To rescue potentially defective HSV in neurons, Brown and coworkers (17) To establish latent infection of HEL cells with HSV-2, we followed previously described protocols (18,19).…”
mentioning
confidence: 99%
“…The explanation for these failures became evident when it was found that the insidious SV40 and/or respective antigens originated from hybrid viruses carrying SV40 and HAdV DNA [77][78][79]. Ironically, it was the selection for these hybrid viruses that allowed the production of the vaccine material in the first place.…”
Section: Adenovirus Vectors: Backgroundmentioning
confidence: 95%
“…The salient properties of the viruses employed in this study are summarized in table 1. The SV40-Ad 7 hybrid virus (E46 + , stock SP2, designated PARA-Ad 7) has been described in detail [2]. 2 additional passages of this virus were carried out in GMK cells prior to this study.…”
Section: Methodsmentioning
confidence: 99%
“…Cells infected with PARA synthesize SV40 tumor (T), U and trans plantation antigens, but no SV40 viral (V) antigen [2][3][4][5]. PARA-Ad 7 can induce SV40-typc tumors in vivo; it is highly oncogenic, whereas the parental Ad 7 is very weakly oncogenic in newborn hamsters [6,7], PARA also ex presses the SV40 function of enhancing human adenovirus replication in cells of simian origin [8].…”
mentioning
confidence: 99%